2005
DOI: 10.1017/s0954579405050248
|View full text |Cite
|
Sign up to set email alerts
|

When adolescents disagree with others about their symptoms: Differences in attachment organization as an explanation of discrepancies between adolescent, parent, and peer reports of behavior problems

Abstract: This study examined whether attachment theory could be used to shed light on the often high degree of discordance between self-and observer-ratings of behavioral functioning and symptomatology. Interview-based assessments of attachment organization, using the Adult Attachment Interview, were examined as predictors of the lack of agreement between self-and other-reports of behavioral and emotional problems among 176 moderately at-risk adolescents. Lack of agreement was measured in terms of concordance of adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
51
3
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 63 publications
8
51
3
1
Order By: Relevance
“…Further, parent-child discordance in ratings of adolescent mental health is highest among adolescents whose relationships with their parents are characterized by insecurity of attachment (Berger et al 2005;Ehrlich et al 2011). These studies lend credence to the idea that discordance may, indeed, be a reflection of the quality of the parent-adolescent relationship and that exploration of the association between parent-adolescent discordance in ratings of parenting practices and aspects of the parentadolescent relationship such as communication, trust and alienation is warranted.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…Further, parent-child discordance in ratings of adolescent mental health is highest among adolescents whose relationships with their parents are characterized by insecurity of attachment (Berger et al 2005;Ehrlich et al 2011). These studies lend credence to the idea that discordance may, indeed, be a reflection of the quality of the parent-adolescent relationship and that exploration of the association between parent-adolescent discordance in ratings of parenting practices and aspects of the parentadolescent relationship such as communication, trust and alienation is warranted.…”
Section: Introductionmentioning
confidence: 65%
“…We argue that such discordance is evidence of poor communication, lack of trust, and heightened alienation among adolescents and parents and, as such, a reflection of a more problematic parent-adolescent relationship. In support of this hypothesis, parent-child discordance in ratings of adolescent mental health is highest among adolescents whose relationships with their parents are characterized by insecurity of attachment (Berger et al 2005;Ehrlich et al 2011), while adolescents whose relationships with their parents are characterized by attachment security are more likely to have open communication and positive relationships with parents and are less likely to report internalizing and externalizing behaviors (Ehrlich et al 2011). Because the quality of parent-adolescent relationships has been found to predict adolescent internalizing and externalizing symptoms (Allen et al 2007;Brumariu and Kerns 2010), we expect that adolescents in discordant adolescent-parent dyads will report higher levels of mental health problems and more problematic relationships with their parents.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Thus, we conceptualize this measure as a proxy for baseline social anxiety because it captures the affective, cognitive and behavioral components of many key social anxiety symptoms in a developmentally appropriate way. The choice to have peer ratings of withdrawal symptoms follows from multiple lines of research suggesting that peer-ratings may overcome some of the biases inherent in using self-ratings of social behavior (Berger, Jodl, Allen, McElhaney, & Kuperminc, 2005;Kobak & Sceery, 1988;Nisbett & Wilson, 1977). The scale has been shown to have good reliability and validity as a marker of childhood vulnerability to psychopathology (Pekarik et al, 1976;Weintraub, Prinz, & Neale, 1978), and internal consistency in the current sample was adequate (Cronbach's α = .…”
Section: Methods Participantsmentioning
confidence: 99%
“…Recent studies have indicated associations between different attachment styles and psychopathology (e.g., Allen et al 2004;Berger et al 2005;Nishikawa et al 2009), and consistent patterns of individual differences in attachment styles among adolescents and young adults (e.g., Markiewicz et al 2006). One series of studies has shown that children and adolescents who classify themselves as avoidant or ambivalently attached display higher levels of Internalizing and Externalizing Problems than adolescents who classify themselves as securely attached (Muris et al 2000;Muris et al 2001;Muris et al 2003).…”
Section: Introductionmentioning
confidence: 99%